Pendidikan Moderasi Beragama Inklusif : Refleksi Kritis Tafsir QS. Al- Hujurat Ayat 10: Penelitian - Yadi, Supri; Komarudin Sassi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Contemporary Islamic education faces serious challenges in responding to the diversity of schools of thought and the potential for intolerance in learning environments. This article aims to critically reflect on QS. al-Hujurat:10 as a theological foundation for developing an inclusive religious moderation education. Using a thematic interpretation approach and literature study, the author examines the exegesis of the verse from classical and contemporary scholars' perspectives and relates it to the current context of Islamic education. The study reveals that the values of Islamic brotherhood, peaceful conflict resolution, and piety as a prerequisite for God's mercy are core principles that can be integrated into Islamic religious learning in schools and pesantrens. Moreover, this article proposes learning strategies based on dialogue, collaborative work, and social reflection as practical implementations of moderation values in education. The findings reaffirm the relevance of QS. al-Hujurat:10 in shaping a tolerant, inclusive generation of Muslims who are ready to become agents of peace in a pluralistic society.